Analysis of the Corruption Effect and Public Governance on State Economic Performance (Case Study in Asia Pasific Countries) - Syarif Yusuf Effendi; Rifki Khoirudin (AIBPM Publisher, 2022)
Corruption is a phenomenon that has received international attention. Corruption practices are very detrimental to the economic sector, accounting for 2% of world GDP or the equivalent of US 1.5 – 2 trillion lost every year due to corruption. The occurrence of corrupt practices is generally due to weak supervision of public officials and the complexity of the bureaucracy which opens up opportunities for corruption. Similar to corruption, the implementation of good governance in government also plays a role in the economic sector. In the global economy, the Asia Pacific region has the best economic prospects and is asked to be the engine of the global economy. But in terms of political integrity and governance, the Asia Pacific region is no better than other regions. Therefore, this study aims to examine the effect of corruption and public governance on the economic performance of Asia Pacific countries in 2004-2020. The results showed that the Corruption Perception Index, Regulatory Quality, and Political Stability had a positive effect on the economy. It is different with population growth which has a negative effect on the economy. Meanwhile, Participation and Accountability do not have a significant effect on the economy. Keywords: Corruption, Public Governance, GDP, Economic Performance, Political Stability.